2020
DOI: 10.1007/s41042-020-00045-5
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Positive School Leadership to Improve Teacher Wellbeing

Abstract: Teacher wellbeing is critical for effective implementation of positive education programs (Quinlan 2017; Slemp et al. 2017). Yet, few studies have explored teachers' experiences of wellbeing, and how to enhance their wellbeing, beyond a focus on their individual practices. This case study examines teachers' perceptions of leadership practices that influenced their wellbeing in an urban high-school in New Zealand. Purposive sampling was used to select three 'high wellbeing' and three 'low wellbeing' teachers, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 74 publications
0
17
0
2
Order By: Relevance
“…Teacher occupational well-being is defined as their responses to cognitive, emotional, health, and social conditions in their work and profession (Viac & Fraser, 2020). The occupational well-being of teachers is further considered to be multidimensional, comprising four core dimensions: cognitive well-being, subjective well-being, physical and mental well-being, and social well-being (Cann et al, 2020). Job crafting is defined as "a specific form of proactive behavior in which the employee initiates change in the level of job demands and job resources" (Tims & Bakker, 2010, p. 14).…”
Section: Job Crafting and Well-being In Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher occupational well-being is defined as their responses to cognitive, emotional, health, and social conditions in their work and profession (Viac & Fraser, 2020). The occupational well-being of teachers is further considered to be multidimensional, comprising four core dimensions: cognitive well-being, subjective well-being, physical and mental well-being, and social well-being (Cann et al, 2020). Job crafting is defined as "a specific form of proactive behavior in which the employee initiates change in the level of job demands and job resources" (Tims & Bakker, 2010, p. 14).…”
Section: Job Crafting and Well-being In Teachersmentioning
confidence: 99%
“…Teacher occupational well‐being is defined as their responses to cognitive, emotional, health, and social conditions in their work and profession (Viac & Fraser, 2020). The occupational well‐being of teachers is further considered to be multidimensional, comprising four core dimensions: cognitive well‐being, subjective well‐being, physical and mental well‐being, and social well‐being (Cann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This finding led to a similar one, posited by Ghavifekr and Pillai [ 54 ], who argued that within a well-organized school climate, the responsibility factor increased job satisfaction. Cann et al [ 115 ] explained how leadership positively influences job satisfaction and enhances well-being, defined as feeling valued, having meaningful professional development, and having a part in decision-making. Chong, Mansur, and Ho [ 116 ] encouraged leadership development for principals, as it increases job satisfaction and teacher retention.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher well-being in the educational system refers to feeling valued, meaningful professional development, and being involved in decision-making. Well-being is achieved mainly when decision-makers, such as principals or school managers, show skills such as relationship building, contextual competence, and social and emotional competence [ 115 ]. The leadership style can have positive effects on job satisfaction by enhancing workforce performance and organizational goals, through motivation and a gradual increase of organizational commitment, as Altaf et al [ 124 ] demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the academic framework, teacher well-being is associated with gratitude, purposeful expert growth, and participation in making decisions. For it to be attained, school administrators must have abilities like making connections, contextual skills, as well as societal and emotive skills ( Cann et al, 2021 ). The leadership method could have a constructive impact on work fulfillment by improving employee presentation and corporate objectives through motivation as well as a slow elevation of commitment ( Altaf et al, 2019 ).…”
Section: Implications and Future Directionsmentioning
confidence: 99%